A Survey on User Authentication Protocols - Prajitha, MV (International Journal of Computer Sciences and Engineering, 2015)
Passwords are the powerful tools that tend to keep all data and information digitally safe. It is frequently noticed that text password remains predominantly popular over the other formats of passwords, due to the fact that it is simple and expedient. However, text passwords are not always sturdy enough and are very easily stolen and misused under different vulnerabilities. Other persons can obtain a text password when a person creates a weak password or a password that is completely reused in many sites. In this condition if one password is hacked, it can be used for all the websites. This is called the Domino Effect. Another unsafe situation is when a person enters his/her password in a computer that is not trust-worthy; the password is prone to stealing attacks such as phishing, malware and key loggers etc. Among the most significant current threats to online banking are keylogging and phishing. These attacks extract user identity and account information to be used later for unauthorized access to user’s financial accounts. This paper focuses on user authentication protocols which are used for secured online processing like online banking. During recent years numbers of authentication protocols are proposed in this area. For further researches, understanding of these approaches is essential.